ANALISIS INDEKS KEPUASAN MASYARAKAT PADA PELAYANAN KANTOR IMIGRASI KELAS I SAMARINDA - Bambang Irawan (Jurnal Administrative Reform, 2017)
This paper aimed to descibe and analyze the degree of public satisfaction towards Samarinda First Class Imigration Office by using public satisfaction index. The method that employed in this paper is decriptive-quantitative where the data take form in numbers and analyzed with statistic-descriptive technique. Scoring system used in this paper was likert scale. The result of the study showed that average score was 3.08 in the interval of 2.51-3.25 so it was included in “good” cathegory.